Strategi Pemasaran Usaha Kuliner di Kepulauan Seribu Utara, DKI Jakarta - Kusumaningrum, Dewi; Hurdawaty, Ramon; Simanjuntak, Vera Clara (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim : The purpose of this research is to find out the marketing strategies carried out by culinary entrepreneurs in the North Thousand Islands. Design/Methode/Approach : This research uses a qualitative approach with descriptive methods. Data collection by field survey methods, documentation, interviews. The research was located on three islands in the North Thousand Islands, namely Kelapa Island, Harapan Island and Pramuka Island, with research time from June to September 2022. Research Finding : The results of the research obtained culinary business marketing strategies which are 1) the target market for consumers is determined, tourists who come to visit the Island, and the surrounding community, 2) culinary product planning includes product types, product processing, packaging and ways of offering to consumers, 3) pricing set by culinary business actors based on production costs which often increase in line with the increase in fuel prices for ships transporting foodstuffs, 4) distribution systems for culinary and catering businesses mostly through intermediaries of tour or travel agents and government officials, 5) general marketing communications conducted conventionally such as direct sales where selling directly to consumers Theoretical contribution/Originality : This research describes the marketing strategy carried out by culinary entrepreneurs in the North Seribu Islands so far where there are still business problems, with this research it can be used as a reference to improve the marketing strategy that has been carried out to increase business. Practitionel/Policy implication : Become a reference in improving the marketing strategy that has been carried out in order to increase business. Research limitation : Limited time for interviews with informants who have busy trading while taking care of the household. Research Contributions: This research can contribute to marketing theory in tourist destinations, local marketing and digital marketing.